Long term care in Romania - Daniela Popa (Center for Social and Economic Research (CASE), 2010)
The increasing life expectancy and the alarming growth in the incidence of chronic illness make long term care services in high demand and in dire need of change and innovation. As part of the ANCIEN initiative, which aims to comprise a database of European approaches for dealing with long term care, this document creates an overview of the health systems organized in Romania which target individuals with long term care needs. The method of governance, the people's needs and the available services are presented herein. For the most part, the services provided in this field are covered through the efforts of the family of those in need and are therefore difficult to quantify or analyze. Public services are either insufficient (in terms of quality or accessibility) and the moral stigma associated to using them prevents families from making this choice. However, due to a high demand and a low supply of high quality LTC services, the private market of nursing homes has exploded in the last few years, funded either privately, through NGOs or external donations. The quality and number of available services has greatly improved but the accessibility is still low. At this moment, Romania still does not have an integrated long term care system neither from the legal or the organization of services being offered. There are social and medical services that are run, provided and legislated independently. The current national strategy is to coordinate these services and to create an integrated system with multidisciplinary teams which would include different types of medical specialists and nurses but still maintain and improve the services offered formally or informally as a home based care package.
Keywords: H51; H55; I18; 330; long-term care; health care system; disability; Romania; Langzeitpflege; Gesundheitswesen; Sozialer Dienst; Sozialpolitik; Rumänien